Childhood Maltreatment, Depression, and Suicidal Ideation: Critical Importance of Parental and Peer Emotional Abuse during Developmental Sensitive Periods in Males and Females - Khan, Alaptagin; McCormack, Hannah C.; Bolger, Elizabeth A.; McGreenery, Cynthia E.; Vitaliano, Gordana; Polcari, Ann; Teicher, Martin H. (Frontiers in Psychiatry, 2015)
BACKGROUND: The Adverse Childhood Experience (ACE) study found that risk for depression increased as a function of number of types of childhood maltreatment, and interpret this as a result of cumulative stress. An alternative hypothesis is that risk depends on type and timing of maltreatment. This will also present as a linear increase, since exposure to more types of abuse increases likelihood of experiencing a critical type of abuse at a critical age. METHODS: 560 (223M/337F) young adults (18-25 years) were recruited from the community without regard to diagnosis and balanced to have equal exposure to 0-4 plus types of maltreatment. The Maltreatment and Abuse Chronology of Exposure scale assessed severity of exposure to 10 types of maltreatment across each year of childhood. Major depression (MDD) and current symptoms were evaluated by SCID, interview and self-report. Predictive analytics assessed importance of exposure at each age and evaluated whether exposure at one or two ages was a more important predictor than number, severity or duration of maltreatment across childhood. RESULTS: The most important predictors of lifetime history of MDD was non-verbal emotional abuse (NVEA) in males and peer emotional abuse (EA) in females at 14 years of age, and these were more important predictors across models than number of types of maltreatment (Males: t9=16.39, p<10-7; Females t9=5.78, p<10-4). Suicidal ideation was predicted, in part, by NVEA and peer EA at age 14, but most importantly by parental verbal abuse at age 5 in males and sexual abuse at age 18 in females. CONCLUSIONS: This study provides evidence for sensitive exposure periods when maltreatment maximally impacts risk for depression, and provides an alternative interpretation of the ACE study results. These findings fit with emerging neuroimaging evidence for regional sensitivity periods. The presence of sensitive exposure periods has important implications for prevention, preemption and treatment of MDD.